Sparking a revolution in groundwater irrigation? Evidence on the impact of electrification on groundwater irrigation markets from a census survey in Bangladesh - Kishore, Avinash; Ray, Shreya; Varshney, Deepak; Radhakrishna, Manikantha; Krupnik, Timothy J. (CGIAR, 2023)
The energy landscape for irrigation in South Asia, has been rapidly changing with the installation of electric pumps. However, there is limited information on the changing energy irrigation nexus in Bangladesh. Using data from a primary census survey of 60 villages (7,500 households) in Rajshahi and Rangpur divisions in northwest Bangladesh conducted in 2023, this research note provides some preliminary evidence on the patterns of electrification of irrigation in these divisions and the evolving behavior and interaction of electric pump owners vis-à-vis diesel pump owners.